Renal Cell Carcinoma: Molecularly Targeted Therapy - Cáceres, William; Cruz-Chacón, Alexis (Puerto Rico Health Sciences Journal, 2011)
Renal cell carcinoma is the most common cancer of the kidney and is among the tumors that are the most resistant to systemic therapy. Until recently, long term survival of this disease when it was not confined to the kidney was dismal, with the use of drugs such as interleukin-2 resulting in a 5-year survival rate of less than 10% for patients with advanced disease. Nearly 30% of patients present with metastatic disease, and recurrence develops in approximately 40% of patients with localized tumors. Since December 2005, the Food and Drug Administration (FDA) has approved 6 novel drugs that target advanced disease. These molecularly targeted drugs, representing the next generation of anticancer agents, inhibit angiogenesis and tumor growth factors. Small molecule tyrosine kinase inhibitors are the prototype of cancer therapy in this century, causing fewer toxic effects in the normal cells and with targeted inhibition of malignant cell proliferation. These therapies have emerged from the understanding of the molecular genetics and biology of this tumor. Further elucidation of the mechanisms of action of these drugs and those in development will lead to more effective therapies and increase the understanding of the best ways to combine them.